A new species of Anthurium (Araceae) from Oaxaca, Mexico - B. Croat, Thomas; de Ávila Blomberg, Alejandro (Instituto de Ecología, A.C., 2015)
Anthurium coicoyanense Croat & de Ávila is described as new from a heretofore poorly collected area in Oaxaca State in Mexico. The species is a member of an as yet unpublished section of the genus that comprises a total of thirteen Mexican species. That section will be proposed formally in an upcoming paper by Croat and Monica Carlsen from the Missouri Botanical Garden.